Overexpression of Tetraspanin31 contributes to malignant potential and poor outcomes in gastric cancer. Issue 6 (1st April 2022) - Takashima, Yusuke; Komatsu, Shuhei; Ohashi, Takuma; Kiuchi, Jun; Kamiya, Hajime; Shimizu, Hiroki; Arita, Tomohiro; Konishi, Hirotaka; Shiozaki, Atsushi; Kubota, Takeshi; Okamoto, Kazuma; Fujiwara, Hitoshi; et al.
Abstract: Tetraspanin has important functions in many cancers by aggregating with various proteins that interact with intracellular signaling proteins. The molecular function of Tetraspanin31 (TSPAN31), located in the 12q14 amplified region in various cancers, remains unclear in gastric cancer (GC). We tested whether TSPAN31 acts as a cancer‐promoting gene through its activation or overexpression in GC. We analyzed seven GC cell lines and 189 primary tumors, which were curatively resected in our hospital between 2011 and 2013. Overexpression of the TSPAN31 protein was frequently detected in three GC cell lines (42.9%) and 62 primary GC specimens (32.8%). Overexpression of TSPAN31 was significantly correlated with lymphatic invasion, venous invasion, more advanced pT and pN stages, and a higher recurrence rate. Moreover, TSPAN31 positivity was an independent factor predicting worse patient outcomes ( p = 0.0283, hazard ratio 3.97). Ectopic overexpression of TSPAN31 facilitated cell proliferation of GC cells, and knockdown of TSPAN31 inhibited cell proliferation, migration, invasion, and epithelial–mesenchymal transition of GC cells through the PI3K‐Akt pathway and increased cell apoptosis in a TP53 mutation‐independent manner. In vivo analysis also revealed knockdown of TSPAN31 suppressed tumor progression. In addition, knockdown of TSPAN31 improved chemosensitivity to cisplatin through the suppression of ABCC2. These findings suggest that TSPAN31 plays a crucial role in tumor‐malignant potential through overexpression, highlighting its utility as a prognostic factor and a potential therapeutic target in GC. Abstract : We showed that Tetraspanin31 (TSPAN31) was frequently overexpressed in primary gastric cancer specimens and related to tumor progression and poor outcomes. Moreover, knockdown of TSPAN31 suppressed cell proliferation, migration, and invasion, as well as improving chemotherapy resistance to cisplatin.